A new Iberian exceptionalism? Comparing the populist radical right electorate in Portugal and Spain - Heyne, Lea (2021)
Since their transition to democracy in the 1970s, Spain and Portugal have been ‘immune’ to the success of populist radical right (PRR) parties. This exceptional situation, however, came to an end: Chega’s leader, André Ventura, was elected in the Portuguese parliament, while VOX has become the third most voted political party of Spain. Using new online survey data from the Spanish and Portuguese national elections in 2019, we find that the Iberian PRR electorate is mostly in line with the characteristics of the PRR electorate in Western Europe when it comes to socio-demographics, political dissatisfaction, media diet, and the rejection of immigration and feminism. Interestingly, however, the support for Chega and VOX does not come from economic losers of globalization. Finally, both parties capitalize on country-specific issues —national unity in Spain and welfare in Portugal— but PRR parties might struggle to establish themselves within the party system of the two Iberian countries.